1998
DOI: 10.1164/ajrccm.157.3.9707158
|View full text |Cite
|
Sign up to set email alerts
|

Hypercapnia Enhances the Development of Coughing during Continuous Infusion of Water into the Pharynx

Abstract: We investigated the effects of increasing CO2 ventilatory drive on the coordination of respiration and reflex swallowing elicited by continuous infusion of distilled water into the pharynx (2.5 ml/min) in 11 normal subjects. Ventilation was monitored using a pneumotachograph and swallowing was recorded by submental electromyogram. The CO2 ventilatory drive was increased by addition of external dead space, while ventilation, the frequency of swallows, and the timing of swallows in relation to the phases of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
49
1

Year Published

2000
2000
2017
2017

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 66 publications
(59 citation statements)
references
References 11 publications
9
49
1
Order By: Relevance
“…However, in COPD patients, the abnormalities in swallow timing within the respiratory cycle [25] are similar to those in neuromuscular patients [19]. In addition, studies in healthy individuals established that the occurrence of inspiration after swallows was increased by hypercapnia [26] or the application of an inspiratory elastic load [27], suggesting that poor breathing-swallowing coordination might be a non-specific sign of respiratory difficulty. Therefore, there is no reason our results would not apply to other populations with respiratory failure.…”
Section: Study Limitationsmentioning
confidence: 92%
“…However, in COPD patients, the abnormalities in swallow timing within the respiratory cycle [25] are similar to those in neuromuscular patients [19]. In addition, studies in healthy individuals established that the occurrence of inspiration after swallows was increased by hypercapnia [26] or the application of an inspiratory elastic load [27], suggesting that poor breathing-swallowing coordination might be a non-specific sign of respiratory difficulty. Therefore, there is no reason our results would not apply to other populations with respiratory failure.…”
Section: Study Limitationsmentioning
confidence: 92%
“…Considering that the swallowing reflex functions as a protective reflex, it is likely that the swallowing reflex interacts with background chemical ventilatory drive. In fact, our previous study [4] showed that hypercapnia not only decreased the frequency of the repetitive swallowing induced by continuous infusion of water into the pharynx but also changed the timing of swallows in relation to the phase of the respiratory cycle.…”
Section: Introductionmentioning
confidence: 94%
“…8), whereas a decrease in CO 2 ventilatory drive has the opposite effect [56]. In addition, it has been reported in a recent study on conscious subjects that the CO 2 ventilatory response is not influenced by continuous reflex swallowing but hypercapnia decreases the frequency of swallows and increases the incidence of laryngeal irritation during continuous infusion of water into the pharyngeal cavity [57]. These observations suggest that the function of protecting the airway subserved by upper airway reflexes may be compromised during hypercapnia or hypoxia.…”
Section: Depression Of Upper Airway Defensive Reflexesmentioning
confidence: 98%